(untitled) (Pedagogy of Higher and Secondary Education, 2002)
The article is devoted to the actual question of lingvodidaсtic which is about the problems on the level of a modern graphic d spelling for students. The basic problem occasions on the level of graphics and spelling in the speech of mass media and the public are analyzed. Accounts the ideas about improving the spelling non of students.